Integrating Students’ Own Cultre in the Teaching of Vocabulary - CHOUAF, Chahrazed (Journal of Human Sciences, 2017)
Many researchers make it evident that culture and language are intertwined. The present paper reports on a study about the usefulness of incorporating learners’ own culture in the teaching of English as a foreign language. More specifically, it aims at investigating the impact of using elements and examples from students’ cultural background to help them learn meanings of unknown vocabulary items presented to them for the first time. It is hypothesized that students are more likely to obtain and correctly guess words’ meanings when these appear in a context which is familiar to them. This study takes as sample first-year LMD students at the Department of Arts and English Language, University of Constantine1. The participants take part in two tests where they have to guess the meaning of a number of vocabulary items from context. The example statements used in the first test are taken from the students’ homeland culture and in the second from the host culture. The findings show that including elements from students’ own culture helped them guess the meaning of new words.